Bibliometric Analysis of Decision-Making in Crisis Management: Mapping Intellectual Structures and Contextual Gaps in Financial Management with Emphasis on Emerging Markets - Nanda Mawadah; Azizah Auliyawati; Hendi Hendi; Akbar Anas Mangkona; Vira Aprilia; Chandika Mahendra Widaryo; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
This study employs a quantitative bibliometric analysis of 102 Scopus-indexed articles to map the intellectual structure of decision-making in crisis management within the financial management domain. Using VOSviewer for co-authorship, keyword co-occurrence, and text-data analyses, the research reveals reactive publication surges following major financial shocks, fragmented collaboration networks dominated by developed economies, and three thematic clusters reflecting a shift from rational-normative models toward hybrid behavioral-technology frameworks. While technology integration shows promising growth, unresolved contradictions persist between behavioral biases and algorithmic solutions. The findings highlight significant contextual gaps, particularly the under-representation of emerging-market perspectives. Theoretically, the study provides a structured intellectual scaffold that integrates macro-systemic dynamics with micro-level behavioral heterogeneity. Practically, it offers guidance for financial managers in volatile environments, with specific relevance to Indonesia where institutional and cultural factors amplify decision-making challenges. The research underscores the need for context-sensitive hybrid models and stronger South-South collaboration to enhance financial resilience in emerging economies facing recurrent global crises.